Physiological mechanical forces accelerate the degradation of bovine lung collagen fibers by bacterial collagenase - Yuqing Deng; Jacob Herrmann; Yu Wang; Minh Nguyen; Joseph K. Hall; Jae Hun Kim; Michael L. Smith; Kenneth R. Lutchen; Elizabeth Bartolák-Suki; Béla Suki (Scientific Reports)
Abstract Collagen fibers, one of the key load-bearing components of the extracellular matrix, contribute significantly to tissue integrity through their mechanical properties of strain-dependent stiffening. This study investigated the effects of bacterial collagenase on the mechanical behavior of individual bovine lung collagen fibers in the presence or absence of mechanical forces, with a focus on potential implications for emphysema, a condition associated with collagen degradation and alveolar wall rupture. Tensile tests were conducted on individual collagen fibers isolated from bovine lung tissue. The rate of degradation was characterized by the change in fiber Young’s modulus during 60 min of digestion under various mechanical conditions mimicking the mechanical stresses on the fibers during breathing. Compared to digestion without mechanical forces, a significantly larger drop of fiber modulus was observed in the presence of static or intermittent mechanical forces. Fiber yield stress was also reduced after digestion indicating compromised fiber failure. By incorporating fibril waviness obtained by scanning electron microscopic images, an analytic model allowed estimation of fibril modulus. A computational model that incorporated waviness and the results of tensile tests was also developed to simulate and interpret the data. The simulation results provided insights into the mechanical consequences of bacterial collagenase and mechanical forces on collagen fibers, revealing both fibril softening and rupture during digestion. These findings shed light on the microscale changes in collagen fiber structure and mechanics under enzymatic digestion and breathing-like mechanical stresses with implications for diseases that are impacted by collagen degradation such as emphysema.